2013
DOI: 10.5194/hessd-10-12077-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Re-suspension of bed sediment in a small stream – results from two flushing experiments

Abstract: Streams draining small watersheds often exhibit multiple peaking sedigraphs associated with single peaking hydrographs. The process reasons of the multiple sediment peaks are not fully understood but they may be related to the activation of different sediment sources such as the streambed itself where deposited sediments from previous events may be available for resuspension. To understand resuspension of stream bed sediments at the reach scale we artificially flooded the small stream of the HOAL Petzenkirchen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 20 publications
3
17
0
Order By: Relevance
“…The processes producing A8 events are difficult to decipher, although the enhanced SSC at low discharges on the rising limb of the hydrograph is likely a result of event water prominence and more specifically, within-channel sediment sources that are readily mobilised during the initial stages of the event (Eder et al, 2014). Such event characteristics…”
Section: Of-eight Hysteresis With An Anti-clockwise Loop (A8) This Imentioning
confidence: 99%
See 2 more Smart Citations
“…The processes producing A8 events are difficult to decipher, although the enhanced SSC at low discharges on the rising limb of the hydrograph is likely a result of event water prominence and more specifically, within-channel sediment sources that are readily mobilised during the initial stages of the event (Eder et al, 2014). Such event characteristics…”
Section: Of-eight Hysteresis With An Anti-clockwise Loop (A8) This Imentioning
confidence: 99%
“…are likely a result of rapid remobilisation of material deposited during the recession period of the previous event (Bull, 1997;Eder et al, 2014). Factor analysis has indicated that the occurrence of these events at Stations A and B is preceded by a combination of fluvial quiescence and relatively high air temperatures.…”
Section: Of-eight Hysteresis With An Anti-clockwise Loop (A8) This Imentioning
confidence: 99%
See 1 more Smart Citation
“…The artificial waves (uniform discharge of 40 l s -1 , volume of 16 m 3 ) were introduced into the channel 450 m upstream of the gauging station. The aim was to monitor the flood wave transformation and the sediment transport within the channel in a way similar to Eder et al (2014). On the basis of the results, it was concluded that the channel does contain sediment from previous erosion events that can be mobilized by even a slight increase of discharge.…”
Section: Complementary Experiments Related To Runoff Generation and Smentioning
confidence: 99%
“…On a recession limb of a hydrograph, the sediment concentration decreases. The reason is that mobile fine-grained particles are quickly flushed from the stream bed, and the flowing water does not have sufficient kinetic energy to carry heavier particles over a long distance (Dostál et al, 2013;Eder et al 2014). …”
Section: Subsurface Runoff Dominationmentioning
confidence: 99%